Predicting Pregnancy in Preconception Weight Loss Trials: Is it Possible? - Jacqueline F. Hayes; Suzanne Phelan; Elissa Jelalian; Aaron B. Caughey; Kristin Castorino; Casey Heaney; Angelica Mchugh; Rena R. Wing (Obesity Science & Practice)
ABSTRACT Introduction Predicting pregnancy is a challenge in preconception weight loss intervention trials. The current study examined whether self‐reported pregnancy likelihood and timing were predictive of conception. Methods Adults (n = 184; 58% Hispanic; age = 33.4 ± 5.1; BMI = 33.6 ± 6.6) with overweight or obesity, prior gestational diabetes mellitus, and plans to become pregnant participated in a pre‐conception behavioral weight loss intervention or control. At baseline, participants reported their estimated likelihood of pregnancy from 1 to 10 (categorized as low [1–3], medium [4–7], and high [8–10] likelihood); they also reported expected timeframe for pregnancy. Results Over the 4‐year trial, 62 (30%) participants became pregnant. Participants who reported a high likelihood of pregnancy were more likely to conceive than those with a lower rating (45.7% vs. 21.1%). The sensitivity and specificity of a high likelihood rating predicting conception were 69%, 95% CI (56.2%, 80.1%), and 58%, 95% CI (48.9%, 67.0%), respectively. Among those who conceived, mean expected time to pregnancy was 21.6 ± 13.2 months while actual mean time was 11.3 ± 9.1 months. Baseline age, ethnicity, parity, BMI, income, and other demographics did not predict conception. Conclusions Pregnancy likelihood estimates best predicted conception, but sensitivity and specificity were low. Future work may consider additional ways to screen for likelihood of conception in preconception trials.